Three-Dimensional Printing Assisted Laparoscopic Partial Nephrectomy vs. Conventional Nephrectomy in Patients With Complex Renal Tumor: A Systematic Review and Meta-Analysis - Yingcheng Jiang; Huimin Zeng; Zewu Zhu; Jinbo Chen; Hequn Chen (Frontiers in Oncology, 2020)
Objective: The purpose of this meta-analysis was to systematically assess the influence of three-dimensional (3D) printing technology in laparoscopic partial nephrectomy (LPN) of complex renal tumors.Methods: A systematic literature review was performed in June 2020 using the Web of Science, PubMed, Embase, the Cochrane library, the China National Knowledge Infrastructure (CNKI), and the Wanfang Databases to identify relevant studies. The data relative to operation time, warm ischemic time, intraoperative blood loss, positive surgical margin, reduction in estimated glomerular filtration rate (eGFR), and complications (including artery embolization, hematoma, urinary fistula, transfusion, hematuria, intraoperative bleeding, and fever) were extracted. Two reviewers independently assessed the quality of all included studies, and the eligible studies were included and analyzed using the Stata 12.1 software. A subgroup analysis was performed stratifying patients according to the complexity of the tumor and surgery type or to the nephrometry score.Results: One randomized controlled trial (RCT), two prospective controlled studies (PCS), and seven retrospective comparative studies (RCS) were analyzed, involving a total of 647 patients. Our meta-analysis showed that there were significant differences in operation time, warm ischemic time, intraoperative blood loss, reduction in eGFR, and complications between the LPN with 3D-preoperative assessment (LPN-3DPA) vs. LPN with conventional 2D preoperative assessment (LPN-C2DPA) groups. Positive surgical margin did not differ significantly.Conclusion: The LPN-3DPA group showed shorter operation time and warm ischemic time, as well as less intraoperative blood loss, reduction in eGFR, fewer complications for patients with complex renal tumor. Therefore, LPN assisted by three-dimensional printing technology should be a preferable treatment of complex renal tumor when compared with conventional LPN. However, further large-scale RCTs are needed in the future to confirm these findings.